Effect of heating rate on the properties of Sb and Mn-doped barium strontium titanate PTCR ceramics - Bomlai P. (2014)
Antimony and manganese-doped barium strontium titanate (BST) ceramics, containing silica and titania sintering additives, were prepared using various heating rates between 1-20°C/min. Crystalline secondary phases of Ba 6Ti17O40 and Ba2TiSi 2O8, formed due to the sintering additives, were found in all samples. The amount of these secondary phases depended on the heating rate. The density of samples reached a maximum value at the two fastest heating rates, 5 and 20°C/min. There was a progressive decrease in grain size from a maximum of 19.7 to 8.3 μm and also an apparently more uniform grain size with increasing heating rate. Consequently, there was a general decrease in resistivity of ρRT and ρmax with increasing heating rate. However, the 20°C/min heating rate gave a slight deviation from this trend; the slightly higher ρRT value for the 20°C/min than the 5°C/min sample may have been due to a higher content of crystallised secondary phases which lead to a higher grain boundary resistivity. © 2004 Elsevier B.V. All rights reserved.